Seasonal and interannual variability in hydrography and currents along the Nansen Legacy transect across the Barents Sea - Sortland, Julie Marie Seime (UiT Norges arktiske universitet, 2023)
The Barents Sea is an Arctic shelf sea that is an important site forwater mass formation and transformation. It is characterized by interactions between Atlanticand Arctic-originWaters, and by strong seasonality in terms of alternating atmospheric and sea-ice conditions throughout the year. How these aspects impact the seasonal evolution of the water column properties is yet to be fully understood. In this study, we investigate the hydrographic conditions along the Nansen Legacy (NL) main transect across the Barents Sea and towards the adjacent Nansen Basin in the Arctic Ocean in the period between 2018 and 2022. In particular, we describe the dominant water masses and currents along the transect and investigate the seasonal and interannual variations in water mass characteristics, distribution, and circulation. The dataset includes CTD, S-ADCP, and L-ADCP profiles collected through the NL project. Ancillary data includes atmospheric reanalysis and remotely sensed sea ice data, used to assess how atmospheric and sea ice forcing alters the water column throughout the study period. Our analysis shows that the NL transects can be divided into three domains reflecting differences in water masses, seasonal evolution, heat- and freshwater content, and flow regimes. In the Nansen Basin and at the Svalbard Continental shelf (81-82◦ N), the circulation is shaped by the water that is advected in with the AtlanticWater Boundary Current (AWBC) at intermediate depths. The seasonal variations of the AWBC further control the seasonal variations in hydrographic properties in the area, for example in the form of elevated oceanic temperatures during autumn/ early winter. In general, the water column structure in the region follows the typical layering with Polar Water (PW) and/or warm Polar Water (wPW) on top followed by Atlantic Water (AW), modified Atlantic Water (mAW), and Eurasian Basin Deep water (EBDW). The Northern Barents Sea (77-81◦ N) is mainly dominated by PW in the upper water column and wPW at lower depths. The water ...